Desenvolvimento de sorvete probiótico a base de leite de cabra: estudo da formulação, características físico químicas, sensoriais e viabilidade das bactérias probióticas - Silva, Priscilla Diniz Lima da (2011)
This work targetet the caprine ice cream production added with probiotic bacteria Bifidobacterium animalis subsp. lactis. It is divided into two parts. In the first one, four caprine ice cream formulations were evaluated, in which it was used hydrogenated fat (F1 and F3) or fat substitute (F2 and F4) in two different flavors (F1 and F2, passion fruit, F3 and F4, guava). Statistical differences (p<0.05) were detected for their physical-chemical properties, mainly for total solids and fat, but no differences were observed for melting test results. When it went to sensory acceptance, all four ice cream formulations reached high acceptance indexes, mostly formulation F4, which was selected for further studies. In the second part, F4 formulation was prepared with the addition of probiotic bacteria Bifidobacterium animalis subsp. lactis. The growth kinetics was studied and it was observed that the cellular concentration peak was reached after four fermentation hours (10.14 log UFC/g). This time was selected for pre-fermentation procedure and posterior addition at ice cream syrup. In this part of the study, two experimental groups were evaluated: group G1, in which the probiotic addition occurred before the maturation step and group G2, which included a pre-fermentation step and probiotic addition after ice cream maturation. The physical-chemical properties of these two ice cream groups were similar, except for pH, which was higher for group G2 (p<0.05). G1 samples had superior melting rate (3.566 mL/min) and both groups presented microbiological and sanitary results in accordance to current Brazilian legislation. Also, G1 and G2 were considered sensory accepted due to their acceptance indexes higher than 70%. G1 and G2 sensory profiles were similar (p>0.05), and both ice cream samples exhibited high creaminess (6.76 to 6.91) and mouth melting sensation (6.53 to 6.67) scores, while low sandiness scores (0.85 to 0.86) were observed, positive characteristics for this kind of food product. During the first 24 hours after ice cream production, the population of B. animalis subsp. lactis decreased, reaching 7.15 e 6.92 log CFU/g for G1 and G2, respectively. Probiotic bacteria counts fluctuated in ice cream samples during the first 108 days at frozen storage, especially for G2 group. Decreased probiotic viability was observed for G1 samples during the first 35 days of frozen storage, mild variation between 35 and 63 days and stabilized counts were observed after this time. After 21 days at frozen storage, ice cream samples of G1 and G2 groups reached 1.2 x 109 and 1.3 x 109 CFU/portion, respectively. After 108 days under these storage conditions, the survival rate of B. animalis subsp. lactis was 94.26% and 81.10% for G1 and G2 samples, respectively. After simulation of gastroenteric conditions, G2 group reached 9.72 x 105 CFU/portion. Considering the current requirements of Brazilian legislation, which stipulates that functional foods must have minimum probiotic count between 108 and 109 CFU/portion and detectable probiotic bacteria after being submitted to gastroenteric conditions, it is concluded that the ice cream with the addition of Bifidobacterium animalis subsp. lactis made as shown in this work, can be considered as a dairy functional food